Губинское захоронение как инструмент создания политического мифа в Азербайджане (Ղուբայում զանգվածաբար թաղվածների գերեզմանոցը՝ որպես քաղաքական միֆի ստեղծման գործիք Ադրբեջանում) - Էլիբեգովա Անժելա (YSU Journal of International Affairs, 2014)
The mass grave discovered in 2007 in the town of Guba in Azerbaijan became the reason for the ruling regime of formation of a new political myth about the "Guba genocide", the originators of which are allegedly the Armenians. The refusal of the Azerbaijani side to conduct an independent examination as well as the contradictions presented during the information campaign that had aroused around these events give a reason to claim that this political myth is artificially created in order to plant stereotype in the Azerbaijani society about the negative role of Armenians in connection with these events.